2001
DOI: 10.1046/j.1365-3059.2001.00571.x
|View full text |Cite
|
Sign up to set email alerts
|

Brown spot caused by Sphingomonas sp. on yellow Spanish melon fruits in Spain*

Abstract: Brown fruit spot symptoms were observed on yellow Spanish melons (Cucumis melo var. inodorus) grown in greenhouses at Almeria in Spain. Nonsporing, motile, rod-shaped bacteria were isolated from diseased fruits, which on nutrient agar produced small yellow colonies. Two bacterial isolates, used for further investigations, were pathogenic on fruits but not on cotyledons of Spanish melon plants. They provoked disease symptoms similar to those observed in the greenhouse. Both isolates were Gram-negative, catalase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…inodorus Naud.) cultivated in greenhouses in Almeria, Spain (Buonaurio et al, 2001). When yellow Spanish melon fruits and leaves were inoculated with the bacterium, only fruits showed disease symptoms.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…inodorus Naud.) cultivated in greenhouses in Almeria, Spain (Buonaurio et al, 2001). When yellow Spanish melon fruits and leaves were inoculated with the bacterium, only fruits showed disease symptoms.…”
mentioning
confidence: 99%
“…When yellow Spanish melon fruits and leaves were inoculated with the bacterium, only fruits showed disease symptoms. 16S rDNA sequence analysis performed on one bacterial isolate revealed that it was phylogenetically closely related to Sphingomonas mali, Sphingomonas pruni and Sphingomonas asaccharolytica (Buonaurio et al, 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This genus has both phytopahtogenic (Buonaurio et al 2001;Deldavleh et al 2013;Kini et al 2017) and plant-beneficial strains, which provide protection against pathogens (Berg and Ballin, 1994;Innerebner et al 2011) and abiotic stress (Halo et al 2015;Asaf et al 2017). These complex relationships of Sphingomonas with plants are an interesting case for future studies on the evolution of plant-microorganism interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Sphingomonas species have frequently been isolated from rice seed (Midha et al , 2016) and have been found on leaves of 26 plant species of 11 families but few are recorded as plant pathogens. Sphingomonas melonis , is the causal agent of a brown spot disease on fruits of Cucumis melo (Buonaurio et al , 2001) and Sphingomonas sp. causes bacterial leaf blight of Paliuris spina‐christi (Deldavleh et al , 2013), The present report seems to be the third case of a plant disease caused by a member of this genus.…”
Section: Figurementioning
confidence: 99%